The effects of proprioception and tactile sensation on visuospatial ability in the upper limb perturbation state of long-term Tai Chi practitioners - Liu, Ziyin; Qi, Wang; Liu, Yanhao; Dong, Shiyu; Song, Qipeng (The Journal of the International Society of Chinese Health Practices, 2024)
See PDF for details